Effects of Biochar Amendment on Potassium Supply Capacity and Potassium Accumulation in Soybean Across Diverse Soils - Liqun Xiu; Yuanyuan Sun; Xiaori Han (Plants, 2025)
Biochar enhances soil available potassium and plant uptake, yet its effects on soil potassium supply capacity and crop potassium accumulation require clarification. This study used a pot experiment with three soil types (albic, brown, and sandy soils) and four biochar application rates (0, 10, 20, and 30 g·kg−1) to investigate potassium supply capacity and soybean potassium accumulation using the potassium site coordination theory and Q/I curve analysis. The results showed that biochar significantly increased the available potassium content in soil. At the highest biochar application rate (30 g·kg−1), the available potassium in the albic, sandy, and brown soils increased by 24.84%, 60.90%, and 24.84%, respectively, compared to the control. The biochar boosted the instantaneous potassium supply (elevated AR0 and ΔK values) through direct water-soluble potassium input. However, the potential potassium supply capacity (PBC) varied by soil type: the PBC increased in the brown soil at low application rates but decreased in the albic and sandy soils with higher rates. The biochar enhanced soybean potassium accumulation through two pathways: the direct enrichment of soil potassium pools and the indirect improvement in soil properties to promote biomass accumulation. These findings provide theoretical insights for optimizing biochar use in agriculture to maximize potassium availability and crop efficiency.